The response of stocks of C, N, and P to plant invasion in the coastal wetlands of China. (14th November 2018) - Wang, Weiqi; Sardans, Jordi; Wang, Chun; Zeng, Congsheng; Tong, Chuan; Chen, Guixiang; Huang, Jiafang; Pan, Haoran; Peguero, Guille; Vallicrosa, Helena; Peñuelas, Josep
Abstract: The increasing success of invasive plant species in wetland areas can threaten their capacity to store carbon, nitrogen, and phosphorus (C, N, and P). Here, we have investigated the relationships between the different stocks of soil organic carbon (SOC), and total C, N, and P pools in the plant–soil system from eight different wetland areas across the South‐East coast of China, where the invasive tallgrass Spartina alterniflora has replaced the native tall grasses Phragmites australis and the mangrove communities, originally dominated by the native species Kandelia obovata and Avicennia marina . The invasive success of Spartina alterniflora replacing Phragmites australis did not greatly influence soil traits, biomass accumulation or plant–soil C and N storing capacity. However, the resulting higher ability to store P in both soil and standing plant biomass (approximately more than 70 and 15 kg P by ha, respectively) in the invasive than in the native tall grass communities suggesting the possibility of a decrease in the ecosystem N:P ratio with future consequences to below‐ and aboveground trophic chains. The results also showed that a future advance in the native mangrove replacement by Spartina alterniflora could constitute a serious environmental problem. This includes enrichment of sand in the soil, with the consequent loss of nutrient retention capacity, as well as a sharp decrease in the stocks of C (2.6 and 2.2 t C ha ‐1 in soil and stand biomass, respectively), N, and P in the plant–soil system. This should be associated with a worsening of the water quality by aggravating potential eutrophication processes. Moreover, the loss of carbon and nutrient decreases the potential overall fertility of the system, strongly hampering the reestablishment of woody mangrove communities in the future. Abstract : Here, we have investigated the relationships between the different stocks of soil organic carbon (SOC), and total C, N, and P pools in the plant–soil system from eight different wetland areas across the South‐East coast of China, where the invasive tallgrass Spartina alterniflora has replaced the native tall grasses Phragmites australis and the mangrove communities The invasive success of Spartina alterniflora replacing Phragmites australis increased the store of P in both soil and standing plant biomass (approximately more than 70 and 15 kg P by ha, respectively) in the invasive than in the native tall grass communities suggesting the possibility of a decrease in the ecosystem N:P ratio with future consequences to below‐ and aboveground trophic chains.